An Economic Criterion for Distributed Renewable Generation Planning. Issue 12 (21st July 2017) - Xiang, Yue; Liu, Yong; Liu, Junyong; Liu, Yilu; Zuo, Kunyu
Abstract: This letter presents a simple temporal-scenario-based economic criterion for planning distributed renewable generation (DRG) in the zone-type distribution network. The advantage of the proposed criterion is that its formulation does not rely on power flow calculations and optimization iterations, thus can quickly indicate the economic feasibility of the DRG unit. A case study has verified its effectiveness, and also indicates that the proposed criterion could calculate the economic attractiveness or resistance for renewable energy investors in this zone.